An Analysis of the Optus National Outage and Recommendations for Enhanced Regulation - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2023)
On Wednesday, 8 November 2023 at about 4am, approximately 10 million Optus retail and 400,000 business customers lost network access as a result of the IP Core network shutdown. Optus stated that the cause of the network outage was a routine software upgrade that led to routing information updates from an international peering network causing key routers to disconnect from the network. This paper provides an analysis of the national outage, what information is needed to fully understand what occurred, and considers the lessons that might be learned.